Directional recombination is initiated at a double strand break in human nuclear extracts. - Lopez, B S (1992)
The involvement of a double strand break in the initiation of homologous recombination was examined in human nuclear extracts. M13 duplex derivatives, containing inserts in the LacZ' region (producing white plaques), were cleaved by restriction enzymes and coincubated in the extracts with a circular plasmid containing the LacZ' region without insert, and unable to produce plaques. Repair was estimated by the ability to produce plaques after transfection into JM109 (recA1) bacteria. Recombination with the plasmid enhances the number of plaques and also the frequency of M13 producing blue plaques. Heterologous insertions in the region surrounding the break were analyzed for their effects on initiation of recombination. The extent of repair by recombination (number of plaques) was compared with the number of blue plaques among the repaired population. Initiation of recombination is inhibited when heterologous insertions are located at 7bp from the break, on the right side as well as on the left side. A low level of recombination is measurable for 27 bp of homology but the maximum efficiency of recombination occurred with homologies of 165 or 320 bp from the break to the heterologous insertion. At 320 bp, the extent of recombinational repair remained at a plateau level but the frequency of blue plaques progressively decreases. We have also analyzed the effect of different sizes of inserts. With longer inserts, a longer length of homology adjacent to the break is required for optimum recombination. However, the size of the insert does not affect the low level of recombination that occurred with a short homology (27 bp). The results indicate that the process is initiated at or near the break, requires homology on both sides of the break and is followed by an elongation from the double strand break to the distal regions of the DNA. Our data provide some support to the double-strand-break repair model established for meiotic recombination in yeast.